Rancang Bangun Aplikasi Posyandu Berbasis Android Menggunakan UML (Studi Kasus: Posyandu Dahlia Perumahan Total Persada) - Devit Fatahila; Diah Rahmawati; Lily Arlianti (JURNAL ILMIAH FAKULTAS TEKNIK, 2023)
This research is focused on the design and development of an Android-based Posyandu application using the Unified Modeling Language (UML) approach. Specifically, it examines the case study of Posyandu Dahlia at Total Persada Housing. The purpose of this research is to provide assistance to developers in designing Android-based Posyandu applications by utilizing UML modeling. The findings of this study indicate that the application of UML significantly enhances the quality and efficiency of system design. UML enables development teams to create applications with a well-organized structure, proper functionality, and optimal interaction between components. Therefore, the use of UML can be considered a highly valuable approach in designing public health applications like Posyandu Dahlia. The aim is for this application to contribute to the tasks of the cadres and participants of Posyandu Dahlia.